2021
DOI: 10.7554/elife.67336
|View full text |Cite
|
Sign up to set email alerts
|

Contingency and chance erase necessity in the experimental evolution of ancestral proteins

Abstract: The roles of chance, contingency, and necessity in evolution is unresolved, because they have never been assessed in a single system or on timescales relevant to historical evolution. We combined ancestral protein reconstruction and a new continuous evolution technology to mutate and select B-cell-lymphoma-2-family proteins to acquire protein-protein-interaction specificities that occurred during animal evolution. By replicating evolutionary trajectories from multiple ancestral proteins, we found that continge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 111 publications
1
25
1
Order By: Relevance
“…90 This observation mirrored the T47A, A63E double mutant discovered in our evolution that demonstrated a small yet significant increase in LC3B binding when compared to the wildtype ULK1 peptide (Figure 5D). These data, along with the mammalian cell coimmunoprecipitation experiment and previous work, 74,80,94 support the theory that observed changes in activity translate beyond the split RNAP system to biologically relevant interactions. While designing and validating rePPI-G we also learned several key lessons in bivalent inducer engineering.…”
Section: ■ Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…90 This observation mirrored the T47A, A63E double mutant discovered in our evolution that demonstrated a small yet significant increase in LC3B binding when compared to the wildtype ULK1 peptide (Figure 5D). These data, along with the mammalian cell coimmunoprecipitation experiment and previous work, 74,80,94 support the theory that observed changes in activity translate beyond the split RNAP system to biologically relevant interactions. While designing and validating rePPI-G we also learned several key lessons in bivalent inducer engineering.…”
Section: ■ Discussionsupporting
confidence: 83%
“…Nonetheless, based on our results here and in previous PACE-based evolutionary campaigns, 91−93 a combination of PANCE/PACS with PACE may be the solution to implementing libraries with rePPI-G. An advantage of the rePPI-G pipeline is that the same split RNAP-based biosensors used for the evolution can also be used to measure target activity in live mammalian cells. 85,86 Most recently, we showcased a PPI evolution system for PACE that features both positive and negative selection, which permitted the rapid reprogramming of PPI specificity via PACE, 94 further demonstrating the potential of PACE-based evolutions and suggesting the rePPI-G platform can be expanded to evolutions of selective molecular glues.…”
Section: ■ Discussionmentioning
confidence: 75%
“…A handful of studies have used deep mutational scanning and experimental evolution techniques to understand the sequence‐function map around extant and ancestral proteins for a few kinds of molecular interactions and forms of allostery. 152 , 153 But we know of no DMS scanning methods at present for homo‐oligomerization or for allosteric control of most functions. Developing high‐throughput bulk assays in which protein sequence can be linked to these features would help to illuminate these issues.…”
Section: Future Directionsmentioning
confidence: 99%
“…Some mutations have different effects when introduced into various presentday proteins, implying epistatic interactions with the substitutions that occurred as these proteins diverged from each other (10)(11)(12)(13)(14); without polarizing and calibrating these differences with respect to time, however, it is not possible to illuminate the rate, direction, or regularity of the process by which the effects of mutations changed during evolution. Ancestral protein reconstruction studies have shown that the effects of particular mutations changed during particular phylogenetic intervals (15)(16)(17)(18)(19)(20)(21)(22), but these works have examined only the beginning and end of an interval and therefore cannot reveal the temporal dynamics of epistasis.…”
mentioning
confidence: 99%